1999
DOI: 10.1023/a:1022658222914
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The Strengths and Difficulties Questionnaire (SDQ) is a brief behavioral screening questionnaire that can be completed in 5 minutes by the parents or teachers of children aged 4 to 16; there is a self-report version for 11- to 16-year-olds. In this study, mothers completed the SDQ and the Child Behavior Checklist (CBCL) on 132 children aged 4 through 7 and drawn from psychiatric and dental clinics. Scores from the SDQ and CBCL were highly correlated and equally able to discriminate psychiatric from dental case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
346
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,165 publications
(363 citation statements)
references
References 8 publications
5
346
1
4
Order By: Relevance
“…This project expands upon previous work (Hudziak et al 2004;Goodman and Scott 1999;Chen et al 1994;Jensen et al 1993), and illustrates the implementation of a scorecard approach. The scorecard was designed to identify relative advantages and disadvantages of each scale through the assessment of diagnostic efficiency and other scale characteristics.…”
Section: Scorecardmentioning
confidence: 75%
See 1 more Smart Citation
“…This project expands upon previous work (Hudziak et al 2004;Goodman and Scott 1999;Chen et al 1994;Jensen et al 1993), and illustrates the implementation of a scorecard approach. The scorecard was designed to identify relative advantages and disadvantages of each scale through the assessment of diagnostic efficiency and other scale characteristics.…”
Section: Scorecardmentioning
confidence: 75%
“…Several studies have examined the relationship between the Child Behavior Checklist (CBCL) and the Strengths and Difficulties Questionnaire (SDQ) (Goodman and Scott 1999;Klasen et al 2000) and demonstrated that both measures assess similar diagnostic categories (e.g., internalizing, externalizing, attention), however, the CBCL addresses a wide range of symptoms, while the SDQ focuses on core symptoms of these common disorders. The Ohio Youth Problem, Functioning, and Satisfaction Scales (OHIO) also query a range of symptoms, but this scale has not been carefully compared to the CBCL or the SDQ.…”
mentioning
confidence: 99%
“…Items were coded as a 3‐ point scale (‘not true,’ ‘somewhat true,’ and ‘certainly true’) where age 7–12 years ( α  = .72). It should be noted that SDQ was found to be at least as efficient at detecting externalizing problems as the Child Behavior Checklist (CBCL; Goodman & Scott, 1999); and associates with ICD‐10 diagnoses of CD and ODD (Goodman, Renfrew, & Mullick, 2000). However, the temper outburst item that is typically the final measure for the SDQ for conduct problems was removed in this study to avoid item overlap between this item and the irritability temper tantrum/outburst item.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, Latent Class Growth Analysis was applied to six assessments of mother--reported CP, spanning the age period from four to 13 years, using the 'Conduct Problem' subscale of the Strengths and Difficulties Questionnaire (Goodman, 2001;Goodman & Scott, 1999) The sum--score at each wave was dichotomized at the standard threshold of four or more (Goodman, 2001), yielding six binary indicators. The four resulting trajectories were described as "Low" (72.4%), "Childhood Limited" (CL, 11.8%), "Adolescent Onset" (AO, 7.8%) and "Early--Onset Persistent" (EOP, 8.0%).…”
Section: Outcome --Conduct Problem (Cp) Trajectories During Childhoodmentioning
confidence: 99%